Metsäklusterin palvelut: Kilpailukykyanalyysi - Esa Viitamo (The Research Institute of the Finnish Economy (ETLA), 2000)
– The globalisation of the competition, the simultaneous saturation of the markets and the complexity of the process technology have increased the importance of service inputs as determinants of competitiveness for the forest industry. At the same time new information technologies have substituted the traditional production inputs such as labour and thus enabled the more efficient production of the services and the increase in their use. From the perspective of the forest industry the most important services for it's competitiveness are engineering services, maintenance services, computer and related services and transportation and logistics. Services are produced by service industries themselves but increasingly also by the forest industry machinery producers, the core business of which is gradually transforming into engineering and maintenance services. The demanding business environment and the globalisation of the forest industry create new opportunities for the internationalisation of these services. The determinants of the over all competitiveness are technological, organisational and market structure based competitiveness. The technology used in the production of the services is very advanced, and it forms a distinct factor of competitiveness for the whole forest cluster. In terms of the market structure the situation within the service branches is in general good, but there is room for improving the market relations between the forest industry and the service companies. The greatest potential in that sense can be found in the organisation of the services.
Keywords: 330; forest industry; cluster; services; competitiveness